2018
DOI: 10.31401/sungeo.2018.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic forcing of the lower stratospheric O3 and surface temperature short-term variability prior to earthquakes

Abstract: This paper is focused on the short-term variations of near surface temperature (T) obtained over a period of one week prior to the earthquake occurrence (EQ). We found a systematic temperature increase in almost the entire examined area (i.e. 8˚-30˚E and 35˚-53˚N), reaching a maximum in Aegean-Balkans-Pannonia basin region. Total of 1039 EQs have been analysed, what ensures statistical significance of our results. Comparison with the spatial distribution of geomagnetic variability reveals a striking similarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Moreover, location and local solar time of the satellite pass also play a vital role in the lower ionospheric dynamics. The observed variability of mesospheric ozone anomaly decreasing (increasing) with increasing (decreasing) altitudes (above/below 70 km) signifying the role of ionospheric electrodynamics along with ion chemistry through atomic oxygen as we go to higher altitude regions in governing the D-region dynamics 21 23 , 33 .
Figure 4 Temporal variation of SABER mesospheric ozone anomaly along with mean VLF amplitude (spline interpolated solid black line) and magnitude of EQs (black circles) for three different regions ( a ) 60 km, ( b ) 65 km and ( c ) 70 km, respectively during April 20 – May 13 2015.
…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, location and local solar time of the satellite pass also play a vital role in the lower ionospheric dynamics. The observed variability of mesospheric ozone anomaly decreasing (increasing) with increasing (decreasing) altitudes (above/below 70 km) signifying the role of ionospheric electrodynamics along with ion chemistry through atomic oxygen as we go to higher altitude regions in governing the D-region dynamics 21 23 , 33 .
Figure 4 Temporal variation of SABER mesospheric ozone anomaly along with mean VLF amplitude (spline interpolated solid black line) and magnitude of EQs (black circles) for three different regions ( a ) 60 km, ( b ) 65 km and ( c ) 70 km, respectively during April 20 – May 13 2015.
…”
Section: Introductionmentioning
confidence: 97%
“…In tandem with observed VLF anomaly 13 during Gorkha Nepal EQ, several simultaneous ionospheric parameters are scrutinized and found that VLF anomaly has a close relation with ozone concentration variation at mesospheric altitudes. Although few studies in the recent past focused on the enhancement of ozone concentration during earthquakes over different parts of the globe by utilizing satellite data along with ground-based observations to better understand the atmospheric variations (columnar ozone, surface temperature, electric field variations) prior to EQs in order to have clarity on the parameters (time, epicentre and magnitude) of the forthcoming earthquakes 21 23 .However, this is the first report to establish a strong relationship between pre-seismic VLF signal amplitude/TT and mesospheric ozone anomalies prior to any major earthquakes over Himalayan region reported till date. Rigorous and detailed analysis is performed with VLF NWC (19.8 kHz) transmitter data recorded at Allahabad (25.41° N, 81.93° E) for two major EQs (EQ1 and EQ2) which occurred within a short span of 20 days apart from the multiple aftershocks subsequent to EQ1 event.…”
Section: Introductionmentioning
confidence: 99%